RESULTS OF IMPLEMENTATION OF TARGET PROGRAMS ON RADIATION ACCIDENT REMEDIATION FOR THE PERIOD TO 2010 AND PROSPECTS OF FURTHER ACTIVITIES - T. A. Marchenko (Радиационная гигиена)
The report contains information about measures undertaken by the Ministry of Civil Defense and Emergencies of the Russian Federation in the framework of implementation of the state policy in the field of radiation accidents remediation. Results of works realized in the framework of target programs on remediation of radiation accidents at Chernobyl NPP and Production Association MAYAK, and on problems caused by nuclear weapon tests at Seminalatinsk test site are presented.